2012
DOI: 10.3747/pdi.2012.00119
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis and the Process of Modality Selection

Abstract: The process of modality selection and how it works is a critical determinant of peritoneal dialysis (PD) utilization. This very complex process has not been well analyzed. Here, we break it down into 6 steps and point out how problems at each step can significantly reduce the proportion of endstage renal disease patients initiating PD. It is important that any program wising it to grow its use of PD understand the steps and the points at which problems may be arising. Examples are presented. Perit Dial Int

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 24 publications
1
74
0
10
Order By: Relevance
“…RRF was not different between the incrPD group and the stPD group, so incrPD was not started at an earlier stage than stPD. It should be noted that to start with incrPD it is necessary to have a good pre-dialysis program and a timely initiation of dialysis; several studies have shown that a good pre-dialysis education program increases the prevalence of patients opting for self-care dialysis [19–25]. As far as adequacy is concerned, patients in both the incrPD group and the stPD group were always above the minimal targets of adequacy [2] even though, as expected, adequacy values were higher on stPD at the beginning of treatment (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…RRF was not different between the incrPD group and the stPD group, so incrPD was not started at an earlier stage than stPD. It should be noted that to start with incrPD it is necessary to have a good pre-dialysis program and a timely initiation of dialysis; several studies have shown that a good pre-dialysis education program increases the prevalence of patients opting for self-care dialysis [19–25]. As far as adequacy is concerned, patients in both the incrPD group and the stPD group were always above the minimal targets of adequacy [2] even though, as expected, adequacy values were higher on stPD at the beginning of treatment (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The DMAR system is a quality assurance system that prospectively measures baseline characteristics and outcomes, including modality changes, hospitalization, transplantation, treatment withdrawal, and death (10)(11)(12). Data are entered by trained clinical staff and reviewed every 90 days by the investigators (M.J.O.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…Although various guidelines and papers differ with respect to potential contraindications for PD (Table 2), [3][4][5][6][7] clinical evidence of ineligibility for PD in these particular circumstances is often lacking. It is our opinion that very few medical contraindications exist for PD.…”
Section: Peritoneal Dialysis: Who?mentioning
confidence: 99%